Top 10 Downloads from ACM's Digital Library. (Communications of the ACM, 2006)
The article presents list of most popular papers, articles and courses regarding computer operating and designing which were downloaded from the ACM's digital library. A paper entitled "The Interactive Performance of SLIM," by Brian K. Schmidt, Monica S. Lam and J. Duane Northcutt which was presented at the "Proceedings of the 17th ACM Symposium on Operating Systems Principles," in December 1999, was rated first among the various papers which were presented in the conference. "Introduction to the Java Programming Language," was considered to be the best course at the ACM professional development center. The most popular articles which were downloaded for reference from the digital library includes "The Profession of IT: Who are We?," by Peter J. Denning published in the February 2005 issue of the journal "Communications of the ACM," "Face Recognition," by W. Zhao, R. Chellappa, P.J. Phillips and A. Rosenfeld published in the December 2005 issue of the journal "ACM Computing Surveys," and "The Business of Software: The Laws of Software Process," by Phillip G. Armour published in the January 2001 issue of the journal "Communications of the ACM."